1988
DOI: 10.1002/jcb.240370405
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropin antagonism of insulin‐stimulated glucose utilization in 3T3‐L1 adipocytes

Abstract: It is well established that somatotropin (GH) antagonizes insulin action in vivo and that supraphysiologic concentrations of GH frequently result in insulin resistance and glucose intolerance. However, the demonstration of an anti-insulin activity by GH in vitro has been difficult. This study, therefore, set out to determine whether cultures of 3T3-L1 adipocytes could be used to examine the anti-insulin activity of GH. The ability of insulin to stimulate glucose utilization by 3T3-L1 adipocytes increases appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, in a homologous lactogenic receptormediated bioassay using bovine mammary gland explants, we found that the native bPL is also as potent as hGH or bPRL (7). Binding experiments to various microsomal fractions revealed that bPL binds with high affinity to prolactin receptors and to somatogenic receptors (2,4,5). In addition, we have documented that bPL binds also to unique receptors in bovine endometrium (8).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…However, in a homologous lactogenic receptormediated bioassay using bovine mammary gland explants, we found that the native bPL is also as potent as hGH or bPRL (7). Binding experiments to various microsomal fractions revealed that bPL binds with high affinity to prolactin receptors and to somatogenic receptors (2,4,5). In addition, we have documented that bPL binds also to unique receptors in bovine endometrium (8).…”
mentioning
confidence: 67%
“…Deglycosylation of native bPL had no effect on PRL-like mitogenic activity in an Nb 2 lymphoma cell proliferation assay in which bPL was equally potent to human (h)GH, bPRL, and ovine (o)PRL, and exhibited only slightly reduced binding to bGH receptors (4). Recombinant bPL was also equally potent to hGH or oGH in somatogenic receptor-mediated 3T3-L1 or 3T3-F442A preadipocyte bioassays (5,6). However, in a homologous lactogenic receptormediated bioassay using bovine mammary gland explants, we found that the native bPL is also as potent as hGH or bPRL (7).…”
mentioning
confidence: 95%
“…In contrast, continuous GH component appears to be predominant in inducing hepatic IGF-I mRNA (6), CYP 3A4 enzymes (10,11), and GH receptors (12). In humans, GH is known to have multiple effects on peripheral tissues, such as promoting somatic growth through generation of IGF-I (6), increasing lipolysis (13), and having antiinsulin effects (14). However, whether these actions were mediated through global GH output or through a pattern-specific exposure of GH pulsatility is largely unknown.…”
mentioning
confidence: 88%
“…The cells were then incubated with insulin in MEM for 6 h. d -[ 14 C(U)]glucose (2.2 dpm/pmol) was then added for 18 h at 37 Њ C in a humidified incubator with 5% C0 2 . The cells were then placed on ice and the medium removed after which the monolayers were washed 3 ϫ with PBS at 4 Њ C. Triglycerides were then extracted for 30 min 2 ϫ with 1 ml isopropanol-heptane (2:3; v/v) and collected after extraction with alum (14,15). The incorporation of d -[ 14 C]glucose into triglycerides was determined by scintillation counting.…”
Section: Triacylglycerol Synthesismentioning
confidence: 99%